The Analysis of Students’ Communication Strategies in Cambridge Curriculum Class - Risma Lestari; Amrina Rosyada; Sherly Citra Putri (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2025)
This researched applied qualitative research to investigate the usage of communication strategies by the students and the context they were used. It was conducted at SMAS Unggulan Harapan Ummat by involving the tenth-grade students of Cambridge Curriculum class as the research subjects. The students’ utterances that contained the usage of communication strategies were the data analyzed in this research. In collecting data, the researcher used observation and recording. It was found that the type of communication strategy most often used by the students was stalling or time gaining strategy. The employment of communication strategies in this research was caused by lack of topic understanding, lack of vocabularies, and lack of grammar or utterances composing. The results of this research could be used as a reflection to determine a suitable method to help students improve their English skills, especially speaking skill. So that students do not depend on the usage of communication strategies to overcome the difficulties in speaking.